Barriers underlying care gaps in Singapore’s mental health landscape and suggestions for improvement from service providers’ perspectives: a qualitative approach - Seah, Siang Joo; Tan, Charlotte Chao Min; Chew, Mary Su-Lynn; Lim, Jin Jin; Mahirah, Dhiya; Ho, Yi-Ching Lynn; Lee, Sing Ai; Lee, Ee-Lian; Yoon, Sungwon; Marimuttu, Vicknesan; Poon, Ngar Yee; Thumboo, Julian (Frontiers in Public Health, 2025)
BackgroundDespite the high prevalence of mental health conditions globally, there are few studies investigating perspectives of providers on barriers underlying care gaps. Therefore, the primary aim of this project was to understand barriers underlying care gaps and suggestions for improvement from mental healthcare service providers in Singapore.MethodsSemi-structured interviews were conducted with 20 mental healthcare providers from public and private sectors, including administrators, practitioners, and an advocate. Participants were recruited via purposive sampling and snowballing. Interview transcripts were analyzed using thematic analysis.ResultsBarriers underlying service accessibility included insufficient integration across organizations and sectors for timely referrals and concerns about stigma of receiving services. Barriers to service effectiveness included limited public sector bandwidth and lack of supervision requirements for private sector allied health practitioners. General practitioners (GPs) faced financial and referral issues when serving as first touchpoint for mental healthcare. Fragmentation of information systems hindered coordinated care implementation, while lengthy referral forms and complex referral routes created additional obstacles. Public sector manpower issues and heterogeneity in frontline staff’s skills for right-siting patients hindered capacity maintenance.ConclusionThese findings highlight systemic challenges related to under-resourcing and a lack of coordination across sectors and organizations, ultimately hindering equitable access to mental healthcare. To address these challenges, recommendations include expanding insurance coverage, strengthening private sector regulation, and reforming reimbursement structures for integrated care. Streamlining referrals and improving data sharing will enhance coordination. Additionally, normalizing mental health conversations, empowering support networks, and increasing access to community-based services will reduce stigma and provide timely care, ultimately improving service delivery and access.